Social Sciences, asked by PoIitician15, 5 months ago

solve the following pair of linear equations by suitable method. 3x-y=3 and 5x-2y=4​

Answers

Answered by TheBrainlyKing1
0

Answer:

  • x=2
  • y=3

Explanation:

according to question

  • 5x-2y=4 and 3x-y=3 . these are the 2 equations that are given.

for finding the value of x put y=3x-3,

  • 5x-2×(3x-3)=4
  • 5x-6x+6=4
  • -x=4-6
  • -x= -2
  • so , x=2

now we know the value of x

put this value in 3x-y=3 equation for finding the value of x.

  • 3(2)-y=3
  • 6-y=3
  • 6-3=y
  • 3=y
  • so,

    the value of y=3.

Answered by peehuthakur
0

Answer:

★ The values are

\large\leadsto\boxed{\tt\purple{x = 2}}⇝

x=2

\large\leadsto\boxed{\tt\purple{y = 3}}⇝

y=3

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀

• Given:-

\sf 3x - y = 3 \dashrightarrow\bf\red{[eqn.i]}3x−y=3⇢[eqn.i]

\sf 5x - 2y = 4 \dashrightarrow\bf\red{[eqn.ii]}5x−2y=4⇢[eqn.ii]

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀

• Solution:-

Firstly,

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀

• Multiplying eqn.[i] by 2:-

➪ \sf 3x - y = 33x−y=3

➪ \sf (3x - y = 3) \times 2(3x−y=3)×2

➪ \sf 6x - 2y = 6 \dashrightarrow\bf\red{[eqn.iii]}6x−2y=6⇢[eqn.iii]

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀

• Subtracting eqn.[ii] from [iii]:-

➪ \sf (6x - 2y) - (5x - 2y) = 6 - 4(6x−2y)−(5x−2y)=6−4

➪ \sf 6x - 2y - 5x + 2y = 26x−2y−5x+2y=2

➪ \sf 6x - 5x = 26x−5x=2

★ \large{\bf\pink{x = 2}}x=2

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀

• Substituting value of x in eqn.[i]:-

➪ \sf 3x - y = 33x−y=3

➪ \sf 3 \times 2 - y = 33×2−y=3

➪ \sf 6 - y = 36−y=3

➪ \sf y = 6 - 3y=6−3

★ \large{\bf\pink{y = 3}}y=3

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀

Therefore, the values are

x = 2

y = 3

Explanation:

Mark me as a brainliest plz

Similar questions